Cardiovascular MR manual - Plein, Sven (Springer, 2011)
The aim of this book is to provide a compact text for practicing physicians and cardiologists or radiologists in training that contains all aspects of cardiovascular magnetic resonance imaging relevant for the appropriate use of this imaging modality in clinical practice. In a tutorial style, the book provides an overview of the relevant physics that govern CMR imaging and provide details on commonly accepted indications for referral. The book also provides the necessary background information to get trainees prepared for training in a CMR center. The emphasis of the book will be on practical.